Inscriptions of the Śilāhāras - Mirashi, Vasudev Vishnu, b. 1893 (Corpus inscriptionum Indicarum, 1977)
Spotlighting the history of 9th to 12th century Maharashtra and Karnataka in the context of the Śilāhāras' regime; inscriptions discovered in the coastal region of Maharashtra, North Konkan.